КАСБ ТАЪЛИМИ ЎҚИТУВЧИЛАРИНИ ТАЙЁРЛАШ СИФАТИНИ ЯХШИЛАШДА ТАРМОҚЛАРАРО АМАЛИЙ ИНТЕГРАЦИЯНИНГ ИМКОНИЯТЛАРИ - Абдураимов, Ш.С. (SCIENCE and SOCIETY, 2016)
The article deals with the analysis of the improvement of pedagogical possibilities in practical inter-sectorial integration to ensure the effectiveness of training teachers of vocational education. The most important section in the system of training is continuous pedagogical training and forming the future specialists in the sphere of vocational education. In pedagogical educational institutions this direction always carries long and continuous character that provides the foundation for the main pedagogical skills and habits in future teachers of vocational education.